Disease activity as a risk factor for myocardial infarction in rheumatoid arthritis. Issue 8 (13th August 2008) - Radovits, B J; Popa-Diaconu, D A; Popa, C; Eijsbouts, A; Laan, R F J M; van Riel, P L C M; Fransen, J
Abstract : Objective: Patients with rheumatoid arthritis (RA) are at greater risk of developing coronary heart disease than the general population. Systemic inflammation may contribute to this risk. This study investigated whether the level of disease activity is associated with the risk of developing myocardial infarction (MI) in patients with RA. Methods: A case-control study was performed within a large prospective cohort of patients with RA. Cases were patients who developed their first MI after the diagnosis of RA, controls were patients with RA without MI. Cases and controls had similar RA disease duration. Traditional and disease-specific risk factors for MI were collected and a time-averaged disease activity score (DAS28) was calculated. The data were analysed using conditional logistic regression analysis. Results: Cases of MI were significantly older, were more often male, with higher body mass index (BMI) and total cholesterol and lower high-density lipoprotein (HDL) serum levels than controls. Time-averaged disease activity was similar for cases and controls. The raw odds ratio for MI in patients with a "high" (>4.0) versus a "low" (⩽4.0) average DAS28 was 1.2 (95% CI 0.61 to 2.36). The odds ratio corrected for age, gender, BMI, baseline Health Assessment Questionnaire and baseline HDL was 0.91 (95% CI 0.39 to 2.12). Conclusion: Patients with RA who developed MI had more classical risk factors but not higher disease activity over time than control patients with RA. Low levels of inflammation may be sufficient for accelerated atherogenesis and an excess risk of cardiovascular disease in RA.